49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-4118
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Analyzing Near-Field Faraday Probe Data of Hall Thrusters

Abstract: This paper presents a new method for analyzing near-field Faraday probe data obtained from Hall thrusters. Traditional methods spawned from far-field Faraday probe analysis rely on assumptions that are not applicable to near-field Faraday probe data. In particular, arbitrary choices for the point of origin and limits of integration have made interpretation of the results difficult. The new method, called iterative pathfinding, uses the evolution of the near-field plume with distance to provide feedback for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…The probe area and the residence time in the plasma are proportional to the total energy transferred to the probe as heat. Past near-field studies of a 20 kW HET plasma demonstrated a probe residence time in the plasma of ∼1 s was acceptable for a probe with frontal area of ∼10 mm 2 at 0.05 TDD from the exit plane [45]. During these studies, the probe translation speed ranged from 150 to 500 mm∕s.…”
Section: Probe Positioning Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The probe area and the residence time in the plasma are proportional to the total energy transferred to the probe as heat. Past near-field studies of a 20 kW HET plasma demonstrated a probe residence time in the plasma of ∼1 s was acceptable for a probe with frontal area of ∼10 mm 2 at 0.05 TDD from the exit plane [45]. During these studies, the probe translation speed ranged from 150 to 500 mm∕s.…”
Section: Probe Positioning Techniquesmentioning
confidence: 99%
“…Spatial variations of plasma properties in EP plumes span orders of magnitude, and they necessitate consideration of the facility interactions with the thruster plasma and probe ion collection. The time-averaged ion current density in the plume of HETs and GITs typically ranges from 1 to 100 mA∕cm 2 in the near-field to less than 0.001 mA∕cm 2 in they periphery of the far-field plume [21,45]. Over this region, the time-averaged electron temperature and ion density range from approximately 10 eV and greater than 10 18 m −3 in the near-field (Z > 0.2D T ) to less than 1 eVand 10 13 m −3 in the far-field plume periphery.…”
Section: A Test Conditions and Plasma Regimesmentioning
confidence: 99%
See 3 more Smart Citations